NO + NH3 reaction over polycrystalline Pt: Numerical analysis of spatio-temporal data and evidence of non-linear behavior - Rafti, Matias (2013)
Surface catalytic reactions display under low pressure conditions non-linear features such as non-stationary reaction rates and spatio-temporal patterns known as dissipative structures. We analyze experimental data from ammonia oxidation reaction over polycrystalline platinum catalyst using quantitative and qualitative nonlinearity tests, such as the Grassberger–Procaccia (GP) algorithm and Surrogate Time Series. Analyses were conducted using local and global information; additionally, we present evidence confirming previously proposed mechanism for the reaction system.